2022
DOI: 10.1038/s41557-022-00908-1
|View full text |Cite|
|
Sign up to set email alerts
|

Porous covalent organic nanotubes and their assembly in loops and toroids

Abstract: Despite the noteworthy progress made in the nanotubular architectures with well-de ned lengths and diameter, the synthesis of a purely covalent bonded organic nanotube, so far, proved to be elusive. Our work includes a hitherto unavailable structure, "Covalent Organic Nanotubes (CONTs)," to the repertoire. Strong covalent bonds between C, N, and O imparts high thermal and chemical stability of CONTs. This novel bottom-up approach provides an edge over the carbon nanotubes (CNTs) in functionalization, synthetic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…Covalently linking organic building units by reticular chemistry has resulted in a versatile and accessible class of porous materials. Porous crystalline structures can be made catalytic, conducting, permeable, and biocompatible using organic building units with defined chemical functionalities combined with controlled and selective synthesis. , We recently reported a design and its implementation to synthesize one-dimensional (1D) porous covalent organic nanotubes (CONTs) . CONTs are one-dimensional, porous, nanotubular frameworks constructed from organic building blocks via reticular chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalently linking organic building units by reticular chemistry has resulted in a versatile and accessible class of porous materials. Porous crystalline structures can be made catalytic, conducting, permeable, and biocompatible using organic building units with defined chemical functionalities combined with controlled and selective synthesis. , We recently reported a design and its implementation to synthesize one-dimensional (1D) porous covalent organic nanotubes (CONTs) . CONTs are one-dimensional, porous, nanotubular frameworks constructed from organic building blocks via reticular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 We recently reported a design and its implementation to synthesize one-dimensional (1D) porous covalent organic nanotubes (CONTs). 6 CONTs are one-dimensional, porous, nanotubular frameworks constructed from organic building blocks via reticular chemistry. The precise orientation of the building units leads to the one-dimensional growth of nanotubes.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 44 46 Recently, the triptycene-based linkers were utilized to construct covalently bonded porous organic nanotubes (CONTs), wherein interesting self-assembly properties were observed. 48 There is only one example of crystalline 2D layered COF built with triptycene monomers that benefits from the superior reversibility of the boronate ester linkage. However, the limited persistence of these boronate ester-based materials hampers their potential for long-term utility.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the use of triptycene-based building blocks to prepare highly crystalline COFs/CPs is rare. The successful examples usually require highly symmetric hexafunctionalized monomers and afford 3D COFs with diverse topologies. For instance, Fang et al demonstrated that the use of triptycene-based building blocks could lead to 3D COFs with remarkable gas adsorption capabilities. Recently, the triptycene-based linkers were utilized to construct covalently bonded porous organic nanotubes (CONTs), wherein interesting self-assembly properties were observed . There is only one example of crystalline 2D layered COF built with triptycene monomers that benefits from the superior reversibility of the boronate ester linkage.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic covalent chemistry has shown great success in the solution synthesis of crystalline organic materials with different dimensionality, such as 1D, , 2D, , and 3D , covalent organic frameworks. Under dynamic covalent chemistry conditions, the covalent bonds between the monomers can be formed and broken; hence, any structural error can be corrected by thermodynamic control.…”
mentioning
confidence: 99%